Advantages of Tissue Level Implants in Case of Alveolar Ridge and Mucosal Atrophy - Kublashvili, Marika; Dolidze, Tamar (European Scientific Journal, ESJ, 2024)
In the modern market, there is a great variety of dental implants, which differ from each other in design, geometry, connection type, surface treatment technology, etc. However, the most fundamental and main differentiating component between implants is how the implants are inserted into the bone and how it is positioned concerning the soft tissues. Accordingly, they are divided into sunken, i.e., bone level implants and non-sunken, i.e., tissue level implants, in which case the implant-abutment connection, or interface, is located at the gum level. This study shows advantages of tissue level - implants in atrophy of the alveolar ridge, also studies comparison of bone loss in case of bone - level implants and tissue level implants.